(3GdYbhHGJ GdSGdHI ddMQjI bUjQI GdeOI hGfYcGSGJgG Ydi HQGeL GdEUdGM hGdJCgjd OGNd GdeDSSGJ GdYbGHjI (B/s - (3eMeO eMeO fHjd eMeO UahJ eMeO agejs; (3YGOd jMj bQfjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2022)
(3gOaJ GdOGQSI Edi(B: (3TQM GdYdGbI Hjf YbhHGJ GdMQeGf bUjQ GdeOi ef GdMQjI hUYhHI JfajP HQGeL GdEUdGM hGdJCgjd ddfRdGA OGNd GdeDSSGJ GdYbGHjI GdeUQjI, hJSdjW GdVhA Ydi HQGeL GdEUdGM hGdJCgjd GdJj CSJbQJ YdjgG GdSjGSI GdYbGHjI GdMOjKI, hCNJjGQ CaVd GdHOGFd aj GdYbhHGJ GdMOjKI GdJj JefY GdMQjI hGdefGSHI ddefGN GdYbGHj aj eUQ(B. (3CTGQJ GdO GQSI Edi(B: (3GdCUhd GdJGQjNjI ddYbhHGJ, JGQjN Yde GdYbGH, JGQjN GdeDSSGJ GdYbGHjI cecGf dJfajP CMcGe GdSLf(B. (3JfGhdJ GdO GQSI(B: (3adSaI GdYbhHGJ GdSGdHI ddMQjI HTcd YGe (B((3GdbjeI GdYbGHjI GdMOjKI, CfhGYgG HGdfSHI ddfXGe GdbGfhfj GdeUQj GdMGdj(B. (3eG jejRgG Yf CfXeI GdYbhHGJ GdCNQi (B). (3JfGhdJ GdO GQSI(B: (3eTGcd GdYbhHGJ bUjQI GdCeO GdJj JMQe GdMQjI Ydi hLg GdNUhU, hJYQjagG, heYGjjQ JMOjOgG, heOi edGAeJgG ddJWHjb aj GdYUQ GdMOjK ,hEjLGHjGJgGhSdHjGJgG, hGdNdGa GdCjOjhdhLj HTCfgG(B. (3CTGQJ GdOGQSI Edi(B: (3HQGeL GdEUdGM hGdJCgjd GdeYGUQI OGNd GdeDSSGJ GdYbGHjI hab GdbhGfjf hGdJTQjYGJ GdChQhHjI GdMOjKI(B. (3aGdJYdje hGdQYGjI GdUMjI hGdGfVHGW GdOjfj hGdCNdGbj gj CMLGQ GdRGhjI aj GdEUdGM GdLfGFj(B. (3HjfJ GdO GQSI(B: (3JMOjO HYV HOGFd GdYbhHGJ GdebjOI ddMQjI hJhVjM WHjYI GdHOGFd GdbGfhfjI hGNJdGagG eY GdCfXeI GdCNQi, hefgG(B( (3GdHOGFd GdbOjeI (B) (3cfXGe hba GdJfajP GdHSjW hGdeTQhW, GdYed ddUGdM GdYGe, eQGbHI GdTQWI, GdZQGeGJ GdeGdjI, (B((3hGdHOGFd GdMOjKI (B) (3cfXGe hba GdJfajP eY GdhVY JMJ GdGNJHGQ, GdeQGbHI GdEdcJQhfjI,CfXeI GdJYhjV Yf CVQGQ GdLQjeI , JCLjd GdfWb HGdMce(B. (3ChUJ GdOGQSI(B: (3JfajP HQGeL JCgjd hEUdGM LjOI OGNd hNGQL GdeDSSGJ GdYbGHjI ef NdGd JfajP NWW GdJOQjH Gdegfj HGeL GdGUdGM GdTGed ef bHd afjjf eJejRjf aj eNJda GdeLGdGJ(B. (3VQhQI JcGed GdCOhGQ GdGLJeGYjI eY GdCOhGQ GdQSejI aj JNWjW hJfajP HQGeL GdEUdGM(B.s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdLfGFj, (B2022s
(3HjTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B247-255s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3YbhHGJ GdMQeGf ef GdMQjIs; (3CZQGV GdYbhHIs; (3GdYed GdYbGHis; (3GdQYGjI GdUMjIs; (3GdeDSSGJ GdYbGHjIs; (3GdJCgjd hGdEUdGMs; (3GdGcQGg GdHOfis; (3GdJUfja GdeHcQs; (3eQGbHI GdHhdjSs; (3hba GdJfajPs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs